2013
DOI: 10.1039/c3gc41403e
|View full text |Cite
|
Sign up to set email alerts
|

Practical metal-free synthesis of chalcone derivatives via a tandem cross-dehydrogenative-coupling/elimination reaction

Abstract: Metal-free synthesis of chalcone derivatives through a tandem cross-dehydrogenative-coupling/elimination reaction is described. A simple and inexpensive ammonium persulfate salt enables the reaction between ketones and benzylamines to proceed with high stereoselectivity and good functional group compatibility.a Reaction conditions: propiophenone 1a (0.5 mmol), benzylamines 2 (2.5 mmol), (NH 4 ) 2 S 2 O 8 (1.5 mmol) in tert-amyl-OH (1.0 mL) at 120 °C for 24 h. b 1 H NMR yield using tetrachloroethane as an inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 32 publications
5
13
0
Order By: Relevance
“…To our delight, NMR studies showed that chloroethoxyamine 2a is observed as the only ring-opening product. After screening different persulfates, in concordance with Zeng [ 32 ], we found that ammonium persulfate ((NH 4 ) 2 S 2 O 8 ) is superior to Na 2 S 2 O 8 and K 2 S 2 O 8 in the transformation, leading to chloroethoxyamine 2a in an excellent yield (93%) in short time.…”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…To our delight, NMR studies showed that chloroethoxyamine 2a is observed as the only ring-opening product. After screening different persulfates, in concordance with Zeng [ 32 ], we found that ammonium persulfate ((NH 4 ) 2 S 2 O 8 ) is superior to Na 2 S 2 O 8 and K 2 S 2 O 8 in the transformation, leading to chloroethoxyamine 2a in an excellent yield (93%) in short time.…”
Section: Resultssupporting
confidence: 76%
“…Based on the above results, a viable mechanism was proposed as shown in Scheme 4 . Initially, aziridine 1a might participate in single-electron transfer (SET) with the persulfate anion to render the radical cation A [ 32 , 34 ]. Concerted ring opening and nucleophilic addition leads to amino radical intermediate B , which is converted to the haloalkoxy amine intermediate 2a after abstraction of one hydrogen atom from alcohol.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…So far there are only two reports available for the oxidative olefination of amines. In 2013, X. Zeng and co‐worker report oxidative olefination of N ‐methyl benzylamines with carbon nucleophiles such as acetophenone by using stoichiometric amount (NH 4 ) 2 S 2 O 8 (Scheme ) . In the same year, Tian and co‐workers described the oxidative olefination of N ‐phenyl benzylamines with carbon nucleophiles such as 2‐ and 4‐methyl pyridine, quinoline, isoquinoline, malononitrile as substrate by using stoichiometric amount of DDQ …”
Section: Introductionmentioning
confidence: 99%
“…It is noteworthy to mention that other uncommon reactions such as the Friedel‐Crafts alkylation, Knoevenagel condensation, and Julia‐Kocienski have also been explored and studied. Other atypical reactions including the olefin cross‐metathesis reaction, the silver‐catalysed double‐decarboxylative cross coupling, bio‐derived ZnO nanoflower and the green metal‐free synthesis via a tandem cross‐dehydrogenative coupling/elimination reaction have also been reported. Propargyl alcohol derivatives have also been used as precursors for isomerization reaction or through the Meyer‐Schuster rearrangement to produce the corresponding enones.…”
Section: Introductionmentioning
confidence: 99%